Respostas

2014-04-27T00:05:52-03:00
 x² - 4x + h + 6 = 0      Se a equação tem duas raízes diferentes, então Δ > 0
a = 1                          
Δ = b² - 4ac
b = -4                         
b² - 4ac > 0
c = h + 6                    
(-4)² - 4 · 1 · (h + 6) > 0
                                   16 - 4h - 24 > 0
                                   -4h > 0 - 16 + 24
                                   -4h > 8                            (multiplicando por -1)
                                    4h < -8
                                      h < -8
                                             4
                                      h < -2